THE EFFECTS OF PEER TUTORING ON DATA STRUCTURE AND ALGORITHM LEARNING ACHIEVEMENT AND TEAM LEARNING BEHAVIORS OF SOFTWARE ENGINEERING AND INFORMATION SYSTEM STUDENTS: ผลการใช้กิจกรรมการเรียนรู้แบบเพื่อนช่วยเพื่อนที่มีต่อพฤติกรรมการเรียนรู้ร่วมกันและผลสัมฤทธิ์ทางการเรียนรายวิชาโครงสร้างข้อมูลและอัลกอริทึมของนักศึกษา สาขาวิศวกรรมซอฟต์แวร์และระบบสารสนเทศ - Thongkaeo, Piyawat (Journal of Education and Innovation, 2019)
The purposes of this study were 1) to study students’ team learning behaviors by the peer tutoring learning management, 2) to compare students’ learning achievement before and after being taught the peer tutoring learning management, 3) to study students’ learning achievement after learning against the 80 percent criterion and 4) to investigate students’ satisfaction after learning being taught the peer tutoring learning management. The research sample consisted of 9 undergraduate students of a Bachelor of Science in Software Engineering and Information System Program who studied in the course of Data Structure and Algorithms at The Faculty of Science and Technology, Pathumwan Institute of Technology. The employed research instruments consisted of a peer tutoring learning management plans, a learning achievement test, a team learning behaviors assessment form and a learning satisfaction assessment form. The research was conducted in classroom action research using one group pretest posttest design. The period of the experiment was for seven weeks with three hours of instruction per a week. The Statistics for data analysis were the mean, standard deviation and t-test. Research findings showed that: 1. The students’ team learning behaviors while learning under the peer tutoring learning management were related at the high level. 2. The students had a learning achievement after using the peer tutoring learning management higher than their pre-learning. 3. The amount of 88.89 percentage students had learning achievement after using peer tutoring learning management were passed the 80 percent criterion. 4. The overall satisfaction of students toward the peer tutoring learning management was related at the high level.